(untitled) (Jurnal Ilmu Komunikasi dan Bisnis, 2022)
Tiktok account @buiramira contains content about tips for dealing with college problems. The purpose of the study was to find out how much effective the communication of the @buiramira tiktok account as a medium of academic education for Riau University students. This study uses a quantitative approach with a descriptive type. The data in this study were obtained from questionnaires distributed online. The population in this study were 29,470 Riau University students as of May 13, 2022. Using the unknown populations formula, a sample of 135 people was obtained. Furthermore, the sampling technique used in this study is accidental sampling. The results of this study indicate that the measurement of the communication effectiveness scale of the @buiramira tiktok account as an educational medium obtained an average of 3.53. Highly effective value and results. This is obtained from the calculation of the communication effectiveness variable according to Cutlip which consists of seven measurement indicators, namely the Credibility indicator with a value of 3.57, Context with a value of 3.59, Content with a value of 3.54, Clarity with a value of 3.50, Continuity and Consistency with a value of 3.44, Channel with a value of 3.62, Capability of The Audience with a value of 3.51. Can be interpreted in several ways. First, the respondent admitted that using tiktok and following the @buiramira tiktok account could help respondents in finding academic information about lectures. Second, the respondent admitted that the tiktok account @buiramira conveyed educational messages in accordance with the problems currently being faced by students. Third, respondents acknowledged that the content of the message in @buiramira’s tiktok content added to students’ academic insight. Fourth, respondents acknowledged that @buiramira’s tiktok content was packaged in clear and easy-to-understand language. Fifth, respondents acknowledged that @buiramira’s tiktok content was consistent and did not change at the time it was uploaded. Sixth, respondents acknowledge that the channel or media used is in accordance with the intended audience. Seventh, respondents admitted that it was easy to absorb the information submitted on the @buiramira . tiktok account.